Risk factors for pleural effusion recurrence in patients with malignancy. Issue 1 (2nd July 2018) - Grosu, Horiana B.; Molina, Sofia; Casal, Roberto; Song, Juhee; Li, Liang; Diaz‐Mendoza, Javier; Reddy, Chakravarthy; Yarmus, Lonny; Schiavo, Dante; Simoff, Michael; Johnstun, Jared; Raid, Abu‐Awwad; et al.
ABSTRACT: Background and objective: The main purpose of treatment in patients with malignant pleural effusion (MPE) is symptom palliation. Currently, patients undergo repeat thoracenteses prior to receiving a definitive procedure as clinicians are not aware of the risk factors associated with fluid recurrence. The primary objective of this study was to identify risk factors associated with recurrent symptomatic MPE. Methods: Retrospective multicentre cohort study of patients who underwent first thoracentesis was performed. The primary outcome was time to fluid recurrence requiring intervention in patients with evidence of metastatic disease. We used a cause‐specific hazard model to identify risk factors associated with fluid recurrence. We also developed a predictive model, utilizing Fine–Gray subdistribution hazard model, and externally validated the model. Results: A total of 988 patients with diagnosed metastatic disease were included. Cumulative incidence of recurrence was high with 30% of patients recurring by day 15. On multivariate analysis, size of the effusion on chest X‐ray (up to the top of the cardiac silhouette (hazard ratio (HR): 1.84, 95% CI: 1.21–2.80, P = 0.004) and above the cardiac silhouette (HR: 2.22, 95% CI: 1.43–3.46, P = 0.0004)), larger amount of pleural fluid drained (HR: 1.06, 95% CI: 1.04–1.07, P < 0.0001) and higher pleural fluid LDH (HR: 1.008, 95% CI: 1.004–1.011, P < 0.0001) were associated with increased hazard of recurrence. Negative cytology (HR: 0.52, 95% CI: 0.43–0.64, P < 0.0001) was associated with decreased hazard of recurrence. The model had low prediction accuracy. Conclusion: Pleural effusion size, amount of pleural fluid drained, LDH and pleural fluid cytology were found to be risk factors for recurrence. Abstract : Factors such as larger pleural effusion size, amount of pleural fluid drained, LDH and pleural fluid cytology were found to be risk factors for pleural fluid recurrence. Knowing what risk factors are associated with recurrence of pleural effusion would allow physicians to identify patients who are more likely to recur.